Developing Higher Order Thinking Skills Assesment Instruments on Invironmental Pollution Material for Class VII - Indah, Asra; Azrita, Azrita; Sari, Rona Taula (Journal of Biological Science and Education, 2021)
The seventh grade science teacher at MTsN 3 Kota Pariaman has problems in developing an instrument for assessing higher order thinking skills. In the 2013 curriculum, teachers are required to be able to provide questions in the C4-C6 domain, namely High Order Thinking Skills (HOTS). This study aim to produce a valid and practical assessment instrument for higher order thinking skills on environmental pollution material at the C4-C6 cognitive level. The background of this research is that the questions made by the teacher are still at the C1-C3 level and there are still obstacles for teachers in developing higher order thinking skills assessment instruments, while inthe 2013 curriculum teachers are required to be able to provide questions in the C4-C6 domain. This type of research is research development (Research and Development) which is a research method used to produce certain products. This type of research uses 3 stages of the 4-D model, namely the define, design and develop stages.Based on the research conducted, a very valid assessment instrument of 3,32 was produced by thevalidator, the empirical validity there were 30 valid questions and 10 invalid questions, the reliability in this study was 0,77 with the category of reliability, 94,79% teacher practicality and practicality. students amounted to 80,80%, the difficulty level of the questions was between 0,31 to 0,70 with moderate criteria and the question difference had sufficient criteria. This research can be used as a reference for other researchers related to the development of higher order thinking skills assessment instruments.Keywords : High Order Thinking Skills, Validity